Studenci o zdrowiu i aktywności fizycznej - Aldona Małyska (Edukacja Ustawiczna Dorosłych)
The article presents the results of a diagnostic survey conducted among students of pedagogy, the aim of which was to find out the respondents’ opinions on health and physical activity undertaken in comparison with a number of restrictions introduced in connection with the coronavirus pandemic. The study presents the definitions of health proposed by the respondents, primarily as the physical and mental well-being of the body and the absence of disease. Among the activities significant for health, the following were listed: regular physical activity, rational diet and preventive medical tests. A significant group of survey participants indicated physical activity, such as: cycling, exercising at home and at the gym, running and walking.